Cost-effectiveness of microscopy of urethral smears for asymptomatic Mycoplasma genitalium urethritis in men in England. (January 2018) - Sutton, Andrew J; Roberts, Tracy E; Jackson, Louise; Saunders, John; White, Peter J; Birger, Ruthie; Estcourt, Claudia
The objective was to determine whether or not the limited use of urethral microscopy to diagnose asymptomatic and symptomatic non-chlamydial, non-gonococcal urethritis (NCNGU) in men is a cost-effective strategy to avert pelvic inflammatory disease (PID), ectopic pregnancy or infertility in female partners. Outputs from a transmission dynamic model of NCNGU in a population of 16–30 year olds in England simulating the number of consultations, PID cases and patients treated over time amongst others, were used along with secondary data to undertake a cost-effectiveness analysis carried out from a health care provider perspective. The main outcome measure was cost per case of PID averted. A secondary outcome measure was cost per major outcome averted, where a major outcome is a case of symptomatic PID, ectopic pregnancy, or infertility. Offering a limited number of asymptomatic men urethral microscopy was more effective than the current practice of no microscopy in terms of reducing the number of cases of PID with an incremental cost-effectiveness ratio of £15, 700, meaning that an investment of £15, 800 is required to avert one case of PID. For major outcomes averted, offering some asymptomatic men urethral microscopy was again found to be more effective than no microscopy, but here an investment of £49, 900 is required to avert one major outcome. Testing asymptomatic men for NCNGU in a small number of genitourinary medicine settings in England is not cost-effective, and thus by maintaining the current practice of not offering this patient group microscopy, this continues to make savings for the health care provider.